1986
DOI: 10.1038/hdy.1986.93
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the colour of the keel petals in Lotus corniculatus L. 3. Pollination, herbivory and seed production

Abstract: The response of pollinators to the pseudo-cryptic polymorphism of dark/light keel colour in Lotus corniculutus has been studied experimentally. Some evidence was obtained that the bumble-bees Bombus lapidarius and B. terrestris forage more dark-keeled flowers in dull and overcast conditions than in bright sunlight.The distribution of herbivorous insects within the flowers of L. corniculatus suggests that they do not distinguish between the keel colour phenotypes.The entire seed production of pre-marked plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Flower color has traditionally been viewed as a trait that is essential in attracting certain suites of pollinators (Grant 1950, Faegri and van der Pijl 1979, Proctor et al 1996. Although many studies have found selective foraging by pollinators for specific color morphs (e.g., Levin 1972, Mogford 1974a, Kay 1976, Hannan 1981, Waser and Price 1981, Brown and Clegg 1984, Jones et al 1986, Stanton 1987a, Stanton et al 1989, Odell et al 1999, Comba et al 2000, Gigord et al 2001, Jones and Reithel 2001, other studies have found pollinators indifferent to flower color variation within a species (e.g., Ernst 1987, Wolfe 1993, Schemske and Bierzychudek 2001. Many pollinator-centric hypotheses have been proposed as factors maintaining flower color polymorphisms, including color preferences and the constancy of specific suites of pollinators to certain color morphs (Stanton 1987a, Jones andReithel 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Flower color has traditionally been viewed as a trait that is essential in attracting certain suites of pollinators (Grant 1950, Faegri and van der Pijl 1979, Proctor et al 1996. Although many studies have found selective foraging by pollinators for specific color morphs (e.g., Levin 1972, Mogford 1974a, Kay 1976, Hannan 1981, Waser and Price 1981, Brown and Clegg 1984, Jones et al 1986, Stanton 1987a, Stanton et al 1989, Odell et al 1999, Comba et al 2000, Gigord et al 2001, Jones and Reithel 2001, other studies have found pollinators indifferent to flower color variation within a species (e.g., Ernst 1987, Wolfe 1993, Schemske and Bierzychudek 2001. Many pollinator-centric hypotheses have been proposed as factors maintaining flower color polymorphisms, including color preferences and the constancy of specific suites of pollinators to certain color morphs (Stanton 1987a, Jones andReithel 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that flower colors could play important roles in attracting or repelling certain pollinators to visit and pollinate flowers. Jones et al (1986) showed that some bees preferred the dark knee color over light color in lotus (Lotus corniculatus L.) for foraging and pollination. Reportedly, white corolla color could limit hybridization of Phlox pilosa L. with pink-flowered Phlox glaberrima L. (Levin and Schaal, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…We are planning an experiment where the fecundities of open-pollinated plants are tested in mixed array m rephcare north and south facing plots. In previously reported experiments, the relative fecundity of dark-and light-keeled plants was tested under uniform conditions and failed to show any temperature related effects (Jones & Crawford, 1977;Jones et al, 1986).…”
Section: Internal Keel Temperaturesmentioning
confidence: 99%
“…There is an interesting report that individuals of Bombus lapidarius L. (but not B. terrestris L.) preferentially forage dark-keeled flowers in overcast weather when presented with both morphs at equal frequency in random array, but not when in a systematic array (Jones et al, 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation